HIV-positive patients' and their families' comprehension of HIV- and AIDS-related information - Gedina E. de Wet; Emmerentia du Plessis; Hester C. Klopper (AOSIS, 2013)
Despite acknowledgement of the importance of sharing HIV- and AIDS-related information with people living with HIV, it is still unclear as to what their actual comprehension is of this information. This research was part of a larger project, Tswaragano, conducted in the North-West Province, South Africa, which explored and described the competence, ability and strengths of the family of the HIV-positive patient during home support. This research focused on Potchefstroom in the North-West Province. This article focuses on research with the objective being to explore and describe the comprehension of HIV-positive patients and their families with regard to HIV- and AIDS-related information, and to formulate recommendations to improve their comprehension of this information. A quantitative, explorative and descriptive survey design was followed. Data were collected by means of questionnaires completed by HIV-positive patients (n= 79) and their family members (n= 34). Descriptive statistical analysis by means of frequency analysis was conducted. Ethical considerations and mechanisms to enhance validity and reliability are discussed. The results indicated that both HIV-positive respondents and their families face social and financial challenges due to unemployment and low income. A strength found in this research is that the majority of respondents are linked to a church, which can be a valuable platform to share information on HIV and AIDS. With regards to sharing, sources and comprehension of HIV- and AIDS-related information, it is apparent that respondents perceived that pre- and post-counselling provided an opportunity for information sharing, but that they need health care workers to spend more time with them, to be non-judgemental and to make more use of visual aids. It furthermore seems that the majority of HIV-positive respondents in this study did comprehend the need for and negotiate for safer sexual practices. It was concluded that although HIV-positive patients and their families have relatively good levels of comprehension of HIV- and AIDS-related information, there are certain gaps in their comprehension of this information. Accordingly, recommendations regarding improving comprehension of HIV-related information were formulated. Recommendations for nursing education, research and practice were formulated. These recommendations highlight the importance of openness in communication, building trust relationships, collaboration, cultural sensitivity and empowering HIV-positive patients and their families.